A study of nitric oxide dynamics in a growing biofilm using a density dependent reaction-diffusion model. (21st January 2020) - Ghasemi, Maryam; Jenkins, Benjamin; Doxey, Andrew C.; Sivaloganathan, Sivabal
Highlights: Oscillatory behavior of NO · concentration under a microaerobic regime is a temporary phenomenon and does not generate gradients in NO · concentration levels within the biofilm. In order to weaken the defense system against NO · (i.e. maximize the inhibitory effects of NO · against bacterial biofilms), large amounts of NO · donor with short half-lives should be used to treat the biofilm. The initial size of a biofilm colony affects the activity of NO · reductants. By decreasing the initial size of biofilm colonies, less reducing agent is produced hence more NO · remains in the system which consequently removes biofilms efficiently. Nutrient deprivation stress can change the NO · dynamics depending on the oxygen and NO · concentration and biofilm size. Thin biofilms respond to starvation stress under microaerobic conditions. In this case, defense system against NO · becomes weak and more biofilms can be eradicated by NO ·. For thick biofilms under microaerobic regimes, starvation prevents NO · from diffusing into the inner region of the biofilms and leads to the layering phenomenon. Abstract: One of a number of critical roles played by NO · as a chemical weapon (generated by the immune system) is to neutralize pathogens. However, the virulence of pathogens depends on the production activity of reductants to detoxify NO ·. Broad reactivity of NO · makes it complicated to predict the fate of NO · inside bacteria and its effects on the treatment of any infection. Here, we present a mathematical model of biofilm response to NO ·, as a stressor. The model is comprised of a PDE system of highly nonlinear reaction-diffusion equations that we study in computer simulations to determine the positive and negative effects of key parameters on bacterial defenses against NO ·. From the reported results, we conjecture that the oscillatory behavior of NO · under a microaerobic regime is a temporal phenomenon and does not give rise to a spatial pattern. It is also shown computationally that decreasing the initial size of the biofilm colony negatively impacts the functionality of reducing agents that deactivate NO ·. Whereas nutrient deprivation results in the development of biofilms with heterogeneous structure, its effect on the activity of NO · reductants depends on the oxygen availability, biofilm size, and the amount of NO ·.